Dampak Kesejahteraan Emosional Relawan Peduly Tangerang pada Bakti Sosial dalam Perspektif Pendidikan Sosial: Penelitian - Zalfa Afrillia; Mawardi Nurullah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to understand how volunteer activities in social service activities affect the emotional well-being of the participants, especially from a social education perspective. This study was conducted on four Peduly Tangerang volunteers involved in social activities in various institutions such as orphanages, nursing homes, disability foundations, and ODGJ foundations. The research method used a descriptive qualitative approach with in-depth interviews. The results showed that participation in social activities resulted in significant changes in the volunteers' emotional condition, such as increased gratitude, happiness, and mental stress. Social activities also serve as an effective means of social learning in fostering empathy and social awareness. Volunteer activities function as a form of non-formal character education that plays a role in building solidarity and sustainable emotional well-being.